1) Cộng từng vế 2 pt của hệ ta đc: xy.(x-y)+x^3-y^3=0\Leftrightarrow xy.(x-y)+(x-y)(x^2+xy+y^2)=0\Leftrightarrow (x-y)(x+y)^2=0\Leftrightarrow \left[ \begin{matrix} x=y\\ x=-y \end{matrix}{} \right.+)Với x=y thay vào pt (1) ta đc 0=2( vô lí)\Rightarrow hệ vô nghiệm+) Với x=-y thay vào pt (2) ta đc : $-2y^3=2\Leftrightarrow y=-1\Rightarrow x=1$Vậy hpt có 1 nghiệm
1) Cộng từng vế 2 pt của hệ ta đc:
xy.(x-y)+x^3-y^3=0\Leftrightarrow xy.(x-y)+(x-y)(x^2+xy+y^2)=0\Leftrightarrow (x-y)(x+y)^2=0\Leftrightarrow \left[ \begin{matrix} x=y\\ x=-y \end{matrix}{} \right.+)Với
x=y thay vào pt (1) ta đc $0=
-2
( vô lí)\Rightarrow
hệ vô nghiệm+) Với x=-y
thay vào pt (2) ta đc : 2y^3=
-2\Leftrightarrow y=-1\Rightarrow x=1$Vậy hpt có 1 nghiệm